KREATIF MEMBELAJARKAN PEMBELAJAR DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN YANG TEPAT SEBAGAI SOLUSI DALAM BERKOMUNIKASI - Atapukang, Nurmasa - (Media Komunikasi Geografi, 2016)
This paper aims to give an overview to the learner to creatively use appropriate learning media to assist learners in achieving the learning objectives that have been formulated. The use of appropriate learning media can help the learners and learners in creating effective communication, so that the learning message delivered by teachers can be understood by students / i, and avoid a miss communication. The use of media in the classroom also requires good planning and careful by at learners. This is necessary because the learners need to sort out which media are suitable and appropriate teaching materials so that the learning objectives can be achieved, the ease in obtaining a medium of learning and use, until the planning of when to use instructional media.Â Keywords: Media Learning